The Zootechnical Factors Affecting the Biosecurity Profile of Fish Farms in the Centre Region of Cameroon: Biosecurity Profile of Fish Farms in the Centre Region of Cameroon - Fonkwa, Georges; KPOUMIE NSANGOU , Amidou; Makombu, Judith Georgette; KAMETIEU DJAMOU, Franck Junior; Tomedi Eyango, Minette; Tchoumboue (Department of Aquaculture, 2024)
In order to optimize the fish production by a better knowledge of preventive measures against fish diseases, a cross-sectional audit was carried out in Cameroon from March to April 2022 on the zootechnical factors affecting the biosecurity practice in fish farms from the Centre Region (3°55'- 4°67'N; 9°46-11°52'E). A total of 50 farms were selected using the